Penerapan Algoritma Naïve Bayes Untuk Diagnosa Hama Pada Tanaman Aglaonema SP dan Monstera Adansonii - M Riandi Widiantoro; Salahudin Robo; Almukarrama Almukarrama (Journal of Computer System and Informatics (JoSYC), 2022)
Aglaonema sp and Monstera Adansonii are the most popular ornamental plants during the COVID-19 pandemic. Aglaonema sp and Monstera Adansonii become the target of the keepers because the colors and patterns on the leaves are unique. Despite the high popularity of Aglaonema sp and Monstera adansonii, not many keepers know the problems faced by their plants. The least number of triggers is knowledge of the keepers in caring for their plants. Therefore, to help the community in maintaining Aglaonema sp and Monstera Adansonii plants, an expert or expert in the field of ornamental plants is takes. Due to the difficulty of finding an expert, a system that is able to keep knowledge from an expert is required. An expert system is part of an intelligence that uses a person's knowledge that is summarized and processed carefully to solve problems. One of the statistical data calculation methods is Naïve Bayes. The Naïve Bayes method is a computational technique for predicting probabilities by calculating how many possible sets by adding up the frequency and combined values ​​of the dataset. The software created is able to share understanding with the community about Aglaonema sp and monstera adansonii plants and what treatment should be given to their ornamental plants